Risk Assessment tool for water reuse - University of Cape Town as a case study - Tendo, Zindzi Sekyana Nabassagi (Department of Civil Engineering, 2026)
The 2015 – 2018 Cape Town drought led to investigations into alternative water sources such as greywater, rainwater, and stormwater. To implement these alternative sources effectively, the associated risks must be understood. The World Health Organisation's Quantitative Microbial Risk Assessment (QMRA) already exists but can be complex, and relevant pathogen data is limited in South Africa. The existing risk assessment framework for irrigation with greywater in South Africa also lacks a detailed risk analysis. Lastly, no tools assess combined risk for the integrated use of greywater, rainwater and stormwater for a context such as Cape Town. This study developed a simplified qualitative risk assessment tool to provide risk management strategies for greywater, rainwater and stormwater. The tool's questions and answers were informed by the QMRA framework and the Irrigation with Greywater framework. Tool users were categorized based on whether they knew what alternative water source they intended to use. The user's answers were then assigned weights reflecting both the probability of exposure and the severity of consequence, with certain answers prioritized due to their substantial impact on elevating risk. From the weightings, a risk profile with an accompanying score ranging from ‘Low-1' to ‘Very High-25' – where higher numbers represent higher risks within a risk category, was assigned based on a risk matrix informed by risk matrices from Nel et al. (2022), World Health Organization (2016), and NRMCC et al. (2006). The tool was tested on four buildings in the study area, i.e., the University of Cape Town: The Hasso Plattner School of Design Thinking Afrika (d-school), the New Lecture Theatre (NLT), the Tugwell residence and the Liesbeeck Gardens residence. The results indicated a high-15 (the high scale was from high-4 to high-15) risk when using untreated rainwater for toilet flushing at the d-school and a very high-25 (highest risk on the very high scale and overall) risk for any alternative water use at the NLT. The Tugwell student residence also exhibited a very high-25 risk for toilet flushing with greywater and stormwater. In contrast, Liesbeeck Gardens showed a moderate-10 (highest risk on the moderate scale of moderate-6 to moderate-10) risk of using rainwater in washing machines across the whole residence, and a very high-25 risk for greywater and stormwater and a moderate-10 risk for rainwater, used in toilet flushing within a flat at the residence. Common risk factors included the presence of tall trees and roof inclination angle for roof-harvested rainwater, proximity to uphill parking lots and motorways for stormwater, and the presence of individuals with low immunity in buildings utilizing greywater. Additionally, the season in which the alternative water source was used significantly influenced the risk profile. The study concluded that the tool can be used to support users in identifying areas of high risk when using these alternative water sources, and therefore aid decision-makers in prioritising resource allocation. The tool can also be used as an educational tool in living labs.